Benjamin Basil Shee, Knight of the Lion and Sun of Persia (1803–1840). Issue 1 (2nd January 2020) - Potts, Daniel
ABSTRACT: Benjamin Basil Shee served as an officer in the armies of 'Abbas Mirza and Mohammad Shah from c. 1827 to 1839. Mentioned in passing by a number of visitors to Iran, he was involved in a surprisingly diverse set of activities, from mountaineering to military campaigns, and knew many of the most important European figures in early Qajar Iran. His career trajectory provides fascinating insight into the many different levels on which European specialists, employed by high-ranking Qajar political élites, functioned and the varied social and political networks in which they participated as actors. Shee's example suggests that we should not underestimate the contributions of European specialists to the social, political, scientific and economic life of nineteenth-century Iran, particularly outside their strict area of professional activity. The rapid dissemination of once obscure sources through the systematic digitisation of libraries in Europe and North America provides a wealth of largely untapped data on many such figures whose names, heretofore, have barely attracted notice in histories of Qajar Iran.